Preferensi gen Z terhadap memilih makanan tradisional atau western di restaurant Trimurti - Sheika Ratu Kirana; Mochammad Musafa'ul Anam; Muhammad Danang Setioko; Gilang Sandhubaya (Jurnal Pariwisata Tourista, 2026)
Restaurant Trimurti is one of the restaurants at the Grand Mercure Malang Mirama Hotel. This study aims to explore the factors that influence Gen Z's decision to choose traditional or Western food at Restaurant Trimurti, focusing on taste, price, accessibility, health, product quality, aesthetics, and personal experience. The method used in this study is a quantitative method that uses primary data through questionnaires. The participants in this study consisted of 109 Gen Z respondents aged 13-28 years who had visited and consumed food at Restaurant Trimurti. The selection of respondents was conducted using purposive sampling based on specific criteria. Data analysis included validity tests, reliability tests, classical assumption tests, and simple linear regression tests. Based on the research results, it was found that among the factors of taste, price, and accessibility, which significantly influence Gen Z's decision in choosing food, the factors of age and attitude toward health have a lower influence. This indicates that Gen Z places greater emphasis on taste, practicality, and comfort compared to age and health. This study is expected to serve as a basis for consideration by culinary businesses, particularly Restaurant Trimurti, in designing menu and marketing strategies that align with Gen Z's needs.